Steel hammer - Bowen, Carl (Bowen, Carl. Shadow Squadron, 2016)
Navy SEAL Lieutenant Commander Ryan Cross and his elite Shadow Squadron have a tall order of a mission ahead of them: parachute onto a moving train and secure a group of hostages, all without letting the terrorist hijackers call in back up.